Financial Sector Assessment Program - Albania : Developing Private Pensions in Albania - World Bank; International Monetary Fund (World Bank, Washington, DC, 2014)
This note sets out options to develop private pensions in Albania. It has been requested by the authorities to help create a more diversified pension system that can deliver improved outcomes for Albania in decades to come. A diversified pension system mixes state and private pensions as well as other sources of retirement income. The analysis, diagnosis, and recommendations use an outcome-based assessment framework. This technical note looks at how the pension system performs relative to 5 key outcomes: efficiency, sustainability, coverage, adequacy, and security. These outcomes depend on the political and economic environment in which a pension system operates, and its overall design including regulatory framework, market structure and conduct, and supervisory approach.